2014
DOI: 10.1007/5584_2014_51
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids Increase Siglec-5/14 Expression in Sputum Cells of COPD Patients

Abstract: Recent studies show that several Siglec receptors, such as Siglec-8 and Siglec-14, may be important therapeutic targets in asthma and COPD. Siglecs are a family of lectins belonging to the immunoglobulin superfamily and recognize sialic acid residues of glycoproteins. Most of Siglecs have intracellular immunoreceptor tyrosine-based inhibitory motifs (ITIM), implicating them in the suppression of immunoreceptor signaling. Siglec-5/14 may be involved in the negative regulation of innate immune responses. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…Although it has been reported that Siglec-5/14 is increased in the sputum of COPD patients as a result of inhaled CSs [16], our in vitro data indicate that monocyte Siglec-14 expression is unaffected by treatment with prednisolone. This would need to be confirmed using patient samples, however, by measuring monocyte Siglec-14 expression levels before and after glucocorticoid treatment.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Although it has been reported that Siglec-5/14 is increased in the sputum of COPD patients as a result of inhaled CSs [16], our in vitro data indicate that monocyte Siglec-14 expression is unaffected by treatment with prednisolone. This would need to be confirmed using patient samples, however, by measuring monocyte Siglec-14 expression levels before and after glucocorticoid treatment.…”
Section: Discussioncontrasting
confidence: 73%
“…It has been reported that inhaled CSs increase Siglec-5/14 expression in the sputum of patients with COPD [16]. Given that CSs are a mainstay of treatment for patients with SLE (Table 1), we sought to determine the effects of overnight prednisolone treatment on donor PBMC Siglec-14 expression.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, Siglec-7 can potentially dampen anti-tumor immunity and promote cancer invasion [ 55 ]. Additionally, it has been demonstrated previously, that glucocorticosteroids increase expression of several Siglecs in immune cells in vivo [ 56 , 57 ]. Given the importance of sialylation and Siglecs in immunity it is reasonable to speculate that Dex can be crucial factor regulating immunogenic potential of gliomas and immunosuppressive phenotype and survival of tumor-associated immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the siglec gene cluster has the Siglec-14 and Siglec-5 genes, while the Siglec-14 null allele contains the Siglec-5/14 fusion gene. Imbalance in Siglec-5/14 expression promotes initiation of inflammatory mechanisms in COPD [94]. The level of Siglec-14 affects the frequency of COPD exacerbations [95].…”
Section: Reviewsmentioning
confidence: 99%